Minas Gerais municipalities and their adherence to the National Food Security System – NFSS (Research, Society and Development, 2023)
The present study seeks to carry out a survey of the municipalities in Minas Gerais that have joined the National Food Security System – NFSS, as a way of guaranteeing the human right to adequate food for their population. For this purpose, a search was carried out in the legislation that deals with the subject, as well as consultation in the information resources made available by the Brazilian and Minas Gerais state governments. The results showed low adherence by municipalities, a worrying fact, since this adherence is an effective instrument to guarantee this right enabling the maintenance of human life with dignity.